HLA and Non-HLA gene polymorphisms in autoimmune hepatitis patients of North Indian adults - Ahuja, Nishtha; Singh, Jagdeep; Minz, Ranjana Walker; Anand, Shashi; Das, Ashim; Taneja, Sunil (Frontiers in Immunology, 2023)
Autoimmune hepatitis (AIH) is a chronic and progressive disease of the liver. This is a multifactorial autoimmune disease with both environmental factors and genetic factors playing a role in its pathogenesis. Certain environmental agents like viruses, drugs, etc., can trigger the disease in a genetically susceptible individual. The present study was aimed to explore the distribution of human leukocyte antigen (HLA)-DRB1, Protein tyrosine phosphatase non-receptor type 22 (PTPN22) and Cytotoxic T-Lymphocyte-associated protein 4 (CTLA-4) polymorphisms in North Indian adult AIH patients and their associations with clinical and pathological characteristics associated with the disease. A total of 147 subjects with 47 cases and 100 healthy controls were enrolled. Diagnosis of AIH was made by Revised International Autoimmune Hepatitis Group scoring system. HLA-DRB1 Typing was done by Luminex-based reverse Sequence-Specific Oligonucleotide Probing (SSOP). Single nucleotide variant (SNV) genotyping for CTLA-4 and PTPN22 was done by simple probe-based SNP arrays. Results indicated SLA positive AIH patients are poor responders to therapy. A significant predispositional association of HLA-DRB1*03 was observed in AIH patients from the North Indian population (p= 0.0001, OR=4.83 (2.30-10.15). The frequency of the GG genotype of CTLA-4 CT 60 was significantly increased in AIH patients compared to controls. Multinomial analysis showed that CTLA-4 CT 60 is an independent predictor for cases.